Pregnancy outcome of gestational diabetes mellitus using a structured model of care : WINGS project (WINGS‐10). Issue 3 (27th December 2016) - Uma, Ram; Bhavadharini, Balaji; Ranjani, Harish; Mahalakshmi, Manni Mohanraj; Anjana, Ranjit Mohan; Unnikrishnan, Ranjit; Kayal, Arivudainambi; Malanda, Belma; Belton, Anne; Mohan, Viswanathan
Abstract: Aim: To evaluate the impact of a structured model of care (MOC) prepared for resource‐constrained settings, on the pregnancy outcomes of Asian Indian women with gestational diabetes mellitus (GDM). Methods: Pregnant women were screened under the Women in India with GDM Strategy (WINGS) MOC for GDM using the International Association of Diabetes and Pregnancy Study Groups criteria. Women with GDM went through a structured MOC that included medical nutrition therapy (MNT), regular physical activity (PA); and insulin when indicated. Fasting blood glucose and post‐prandial blood sugar were monitored every 2 weeks. The pregnancy outcomes of women with GDM who underwent the MOC were compared with those without GDM. Results: Under the MOC, 212 women with GDM were followed through pregnancy, of whom 33 (15.6%) required insulin and 179 (84.4%) were managed with MNT and PA. The maternal and neonatal outcomes of women with GDM were similar to the non‐GDM women: there were no significant differences in pregnancy complications such as cesarean section, macrosomia, pre‐eclampsia, oligo/polyhydramnios, preterm delivery, neonatal death, fetal distress, hyperbilirubinemia and low birthweight. Conclusion: Implementation of a structured MOC for women with GDM helped achieve pregnancy outcomes similar to those without GDM.